Pengembangan Media Pembelajaran Berbasis Aplikasi Android Pada Pendekatan Matematika Realistik Pokok Bahasan Pola Bilangan - Huri, Daman; Sulistyaningrum, Heny (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
This research was motivated by the results of observations by researchers at MTs Hidayatul Mubtadiin Sarang Class VIII-B, where information was obtained that during the Covid19 pandemic students studied online which made students bored and did not understand learning material, especially mathematics. Therefore, making this media is very suitable for learning during a pandemic like this. With media that uses smartphone applications, it is hoped that students will be interested in understanding the concept of learning mathematics, especially in this number pattern material even better. The product produced in this research is an Android-based media for realistic mathematics learning, namely software (software) with the extension *apk which can only be run on the Android operating system. This study uses an R&D model which has 4 stages, namely the define stage, the design stage, the develop stage and the disseminate stage. Research and development is understood as a research activity that begins with research (research) then continues with development (development). Media developed using the construct 2 application. The media that was developed was then tested for validity until it was declared valid and then implemented to determine the practicality and effectiveness of the product.